2017
DOI: 10.1787/a8756593-en
|View full text |Cite
|
Sign up to set email alerts
|

Nurses in advanced roles in primary care

Abstract: All Health Working Papers are now available through the OECD website at: http://www.oecd.org/els/health-systems/health-working-papers.htm JT03422943 This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 68 publications
1
52
0
5
Order By: Relevance
“…APN refers to nursing beyond the level of front-line nursing that maximizes the use of graduate educational preparation, in-depth nursing knowledge, and expertise (Delamaire & Lafortune, 2010;Maier et al, 2017 ;Sheer & Wong, 2008). The umbrella term "APN" encompasses various types of roles such as clinical nurse specialist and nurse practitioner (NP), which are the two most common APN roles internationally (Maier et al, 2017;Sheer & Wong, 2008). Studies have revealed several, even hundreds, of job titles in use (Leary, Maclaine, Trevatt, Radford, & Punshon, 2017;Pulcini, Jelic, Gul, & Loke, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…APN refers to nursing beyond the level of front-line nursing that maximizes the use of graduate educational preparation, in-depth nursing knowledge, and expertise (Delamaire & Lafortune, 2010;Maier et al, 2017 ;Sheer & Wong, 2008). The umbrella term "APN" encompasses various types of roles such as clinical nurse specialist and nurse practitioner (NP), which are the two most common APN roles internationally (Maier et al, 2017;Sheer & Wong, 2008). Studies have revealed several, even hundreds, of job titles in use (Leary, Maclaine, Trevatt, Radford, & Punshon, 2017;Pulcini, Jelic, Gul, & Loke, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed several, even hundreds, of job titles in use (Leary, Maclaine, Trevatt, Radford, & Punshon, 2017;Pulcini, Jelic, Gul, & Loke, 2010). The array of titles used is found a problematic issue in several countries across Europe causing disparity and confusion (Dury et al, 2014;Leary et al, 2017;Maier et al, 2017;Mohr & Coke, 2018). Recently, some organizations have begun to develop frameworks for APN; however, there is a paucity of information guiding the policymaking or practice implementation process (Chang, Gardner, Duffield, & Ramis, 2012;Schober, Gerrish, & McDonnell, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Québec is one province in Canada; the government will add 2,000 NPs over the next decade to improve access to and quality of primary care in different settings, including LTC. Graduate-level university education and experience allow NPs to treat acute conditions, monitor stable chronic conditions and prescribe and monitor medications and tests (Maier, Aiken, & Busse, 2017; Ordre des infirmières et infirmiers du Québec, & Collège des médecins du Québec, 2014). International studies demonstrate that NPs increase access to services in LTC (Joanna Briggs Institute, 2010).…”
Section: Introductionmentioning
confidence: 99%